2009
DOI: 10.4103/0971-5851.65343
|View full text |Cite
|
Sign up to set email alerts
|

Cancer lung: An unusual presentation

Abstract: Phalanx bone metastasis as the initial manifestation of lung cancer is a rare presentation. A 70-year-old man presented with swelling and pain in his right ring finger. He had no other complaints or abnormal findings on clinical examination. A right hand radiograph showed an osteolytic lesion in the first phalanx of the ring finger. Fine needle aspiration cytology of the swelling suggested a metastatic adenocarcinoma. A skeletal survey, hematological, biochemical, and other radiological tests were found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
1
Order By: Relevance
“…It can be easily confused with an infection; an X-ray can be very helpful. Pathology may be necessary in case of doubt and additional exams such as chest CT and bronchoscopy should be performed to identify the primary lesion [ 5 ]. Bone scintigraphy is a good exam to identify other bone lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It can be easily confused with an infection; an X-ray can be very helpful. Pathology may be necessary in case of doubt and additional exams such as chest CT and bronchoscopy should be performed to identify the primary lesion [ 5 ]. Bone scintigraphy is a good exam to identify other bone lesions.…”
Section: Discussionmentioning
confidence: 99%
“…1 Despite their primary origin of tumor, they comprise only 0.1% of all osseous metastatic disease. 2 Acrometastasis originating from a primary lung cancer will commonly have a presentation similar to that of diabetic ulcers or even osteomyelitis. Tey can present as painful lesions that are swollen and erythematous, and trauma may often be associated in the patient's history, as with the patient in this case.…”
Section: Discussionmentioning
confidence: 99%
“…In the hand, the distal phalanges are the most common sites of metastatic deposits. 2 Andreani and colleagues have reported that the most common site of acrometastases in the foot are the proximal locations, with tarsal bones being the most common at 50%, followed by the calcaneus, metatarsal, and phalanx bones in decreasing frequency. 5 Nicholson and colleagues have also described a case of cutaneous metastasis to a digit with ultimate bone invasion from the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In einer Arbeit von Jakhar et al manifestierte sich z. B. ein Bronchialkarzinomdem in bis zu 50 % der Fälle die Knochenmetastasen der Hände entstammenerstmalig an den Finger mit einer schmerzhaften Schwellung [37]. Der primäre Knochenbefall durch Lymphome ist ebenfalls selten und hat einen Anteil von 3 % an allen malignen Knochentumoren [38].…”
Section: Gradunclassified